Motorische Kontrolle beim Stehen und Gehen - ein Vergleich von Personen mit und ohne unspezifische Schmerzen im unteren Rücken - Koch, C. C. (2019)
Non-specific low back pain poses a major socioeconomic problem. Further-more, it restricts each affected individual in his/her daily activities. To better understand the possible underlying mechanisms, the aim of the present work is to compare motor control between individuals with and without non-specific low back pain. Two systematic analyses of literature were performed according to the guide-lines of the PRISMA statement. Considering motor control during standing and walking, the systematic search in five databases results in 21 studies on quiet standing and 31 studies on walking (published between January 2000 and January 2018), which investigated individuals with and without non-specific low back pain (NSLBP) using biomechanical or neuromuscular parameters. The data extraction and the evaluation of study quality were performed by two independent persons. For example, data of the sample were extracted and evaluated. Characteristics of the sample were used for the evaluation of the quality of studies. The results for quiet standing indicate differences in motor control during standing between individuals with and without NSLBP. Even though the majority of included studies showed only moderate quality and only a few high quality studies exist, there is an indication for a stiffened pelvis-spine region through an increased activation of the hip and back muscles as well as a shift of proprioceptive weighting towards the use of ankle strategy in individuals with NSLBP. Furthermore, differences in the oscillation of the center of pressure are found with more challenging conditions like bandaged eyes or unstable surface. There is no evidence of differences in the joint angles during standing. The results for walking confirm differences in motor control between individuals with and without NSLBP. Due to only a few high quality studies there is also no high evidence of differences in any of the parameters, but concerning the biomechanical parameters there is at least a tendency for a lower preferred walking velocity on the treadmill, a lower amplitude of pelvis motion, more in phase coordination, lower ground reaction forces and a higher stride-to-stride variability in the NSLBP group. Moderate evidence has been found in EMG data for a higher activity of the erector spinae (ES) in the NSLBP group. Taken together the results for standing and walking point to an altered motor control, that is indicated by a higher ES activity and leads to a stiffened lumbar spine-pelvis region, an increased use of ankle strategy, higher oscillations un-der challenging conditions, and a compounding coordination. Based on these results a case-control-study was conducted to replicate the results. The study has been preregistered on the OSF platform. Biomechanical and neuromuscular parameters were acquired simultaneously. During standing the displacement of the center of mass as well as the activity of the ES were collected. During walking preferred velocity, ground reaction forces (GRF), pelvis to thorax rotation, variability of the rotation of pelvis to thorax and activity of the ES were collected. Twenty individuals with and without NSLBP participated in the study. Participants were matched according to age and sex. During standing three trials à 90 seconds for each of the three different conditions (standing on solid ground with eyes open, standing on solid ground with eyes bandaged and standing on unstable surface with eyes open) were performed. Via force platform, the data of the center of mass and via surface EMG muscular activity of ES were collected. During walking three trials with a preferred walking speed were performed on an 8m walkway. Afterwards participants had to walk at a given speed until they completed three trials at the given speed of 1.2 m/s with the right foot stepping onto the force platform during walking. With the force platform the GRF were recorded, while smartphones, which were attached to the pelvis and thorax, recorded the motion of the pelvis to thorax. Due to technical issues EMG data during walking could not be analyzed. After the execution of the tests all participants had to fulfill a questionnaire about their current mood, pain intensity, well-being, disabilities, and physical activity. A current pain intensity of M=2.6 and a pain intensity of M=5.1 in average over the last six weeks for the NSLBP group was reported. The control group rated their current pain with M=0.1 and M=0.5 in average over the last six weeks. For well-being there were only differences between groups on the physical scale, not on the psychic scale. The average disability in the NSLBP group was low. No significant differences between groups could be found for physical activity. A multivariate testing for standing shows a main effect for conditions which results from the higher Co M displacement during standing on foam compared to the other conditions. There is no significant main effect for group. A significant interaction between group and condition cannot be found either. In the present study differences between individuals with and without NSLBP concerning neuromuscular and biomechanical parameters during standing cannot be confirmed. A multivariate testing for walking does not show a significant main effect for group. Accordingly, differences in motor control between groups cannot be replicated for walking either. An analysis of correlations between control variables and parameters of motor control revel no considerable effects. Possible reasons for these result scan be found in the complexity of control processes, the low demand of the tasks, the relatively good fitness level, the high inter-individual variability of the dependent variables and the possibility, that parameters like minimal Co M-displacement are not accurate. In conclusion, with the case control study the parameters identified through the systematic analyses of literature could not be replicated. Since the findings of existing research are heterogeneous, differential effects seem to be possible and indicated by our findings. In the future itis necessary to clear the relation between NSLBP and differences in motor control by performing long term studies, using superordinate parameters, as well as using pattern analysis.